5. (3 + x) + 3. (2 + x) = 37
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 4 x 76 + 76 x 7
= (4 + 7) x 76
= 11 x 76
= 836
b) 4 x 54 + 54 x 2 + 5 x 54
= (4 + 4 + 5) x 54
= 13 x 54
= 702
c) 37 + 3 x 37 + 5 x 37 + 2 x 37
= 37 x (3 + 5 + 2)
= 37 x 10
= 370
a) 4 x 76 + 76 x 7
= (4 + 7) x 76
= 11 x 76
= 836
b) 4 x 54 + 54 x 2 + 5 x 54
= (4 + 4 + 5) x 54
= 13 x 54
= 702
c) 37 + 3 x 37 + 5 x 37 + 2 x 37
= 37 x (3 + 5 + 2)
= 37 x 10
= 370
d) Ta có: \(32\%-0.25:x=-\dfrac{17}{5}\)
\(\Leftrightarrow0.25:x=\dfrac{8}{25}+\dfrac{17}{5}=\dfrac{93}{25}\)
hay \(x=\dfrac{25}{372}\)
Vậy: \(x=\dfrac{25}{372}\)
e) Ta có: \(\left(x+\dfrac{1}{5}\right)^2+\dfrac{17}{25}=\dfrac{26}{25}\)
\(\Leftrightarrow\left(x+\dfrac{1}{5}\right)^2=\dfrac{9}{25}\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{5}=\dfrac{3}{5}\\x+\dfrac{1}{5}=-\dfrac{3}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{5}\\x=-\dfrac{4}{5}\end{matrix}\right.\)
Vậy: \(x\in\left\{\dfrac{2}{5};-\dfrac{4}{5}\right\}\)
f) Ta có: \(-\dfrac{32}{27}-\left(3x-\dfrac{7}{9}\right)^3=-\dfrac{24}{27}\)
\(\Leftrightarrow\left(3x-\dfrac{7}{9}\right)^3=\dfrac{-8}{27}\)
\(\Leftrightarrow3x-\dfrac{7}{9}=-\dfrac{2}{3}\)
\(\Leftrightarrow3x=\dfrac{1}{9}\)
hay \(x=\dfrac{1}{27}\)
g) Ta có: \(60\%\cdot x+0.4x+x:3=2\)
\(\Leftrightarrow\dfrac{4}{3}x=2\)
hay \(x=\dfrac{3}{2}\)
Vậy: \(x=\dfrac{3}{2}\)
h) PT \(\Leftrightarrow\left|\dfrac{20}{9}-x\right|=\dfrac{2}{9}\) \(\Rightarrow\left[{}\begin{matrix}\dfrac{20}{9}-x=\dfrac{2}{9}\\x-\dfrac{20}{9}=\dfrac{2}{9}\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{22}{9}\end{matrix}\right.\)
Vậy ...
i) PT \(\Leftrightarrow\dfrac{8}{5}+\dfrac{2}{5}x=\dfrac{16}{5}\) \(\Leftrightarrow\dfrac{2}{5}x=\dfrac{8}{5}\) \(\Leftrightarrow x=4\)
Vậy ...
+) \(\dfrac{1}{3}x=-\dfrac{4}{3}-\dfrac{1}{2}=-\dfrac{11}{6}\)
\(x=-\dfrac{11}{6}:\dfrac{1}{3}=-\dfrac{11}{2}\)
+) \(\dfrac{4}{3}x=-\dfrac{2}{3}+\dfrac{1}{2}=-\dfrac{1}{6}\)
\(x=-\dfrac{1}{6}:\dfrac{4}{3}=-\dfrac{1}{8}\)
+) \(2\left(x-1\right)=\dfrac{5}{2}+\dfrac{2}{3}=\dfrac{19}{6}\)
\(x-1=\dfrac{19}{12}\)
\(x=\dfrac{31}{12}\)
\(\dfrac{1}{3}x+\dfrac{1}{2}=-\dfrac{4}{3}\)
\(\dfrac{1}{3}x=\left(-\dfrac{4}{3}\right)-\dfrac{1}{2}\)
\(\dfrac{1}{3}x=-\dfrac{11}{6}\)
\(x=\left(-\dfrac{11}{6}\right):\dfrac{1}{3}\)
\(x=-\dfrac{11}{2}\)
\(-\dfrac{2}{3}-\dfrac{4}{3}x=-\dfrac{1}{2}\)
\(\dfrac{4}{3}x=\left(-\dfrac{2}{3}\right)-\dfrac{-1}{2}\)
\(\dfrac{4}{3}x=-\dfrac{1}{6}\)
\(x=\left(-\dfrac{1}{6}\right):\dfrac{4}{3}\)
\(x=-\dfrac{1}{8}\)
\(\dfrac{5}{2}-2\left(x-1\right)=-\dfrac{2}{3}\)
\(2\left(x-1\right)=\dfrac{5}{2}-\left(-\dfrac{2}{3}\right)\)
\(2\left(x-1\right)=\dfrac{19}{6}\)
\(\left(x-1\right)=\dfrac{19}{6}:2\)
\(x-1=\dfrac{19}{12}\)
\(x=\dfrac{19}{12}+1\)
\(x=\dfrac{31}{12}\)
a)45*32+210*30=210*9+210*30=210*(9+30)=210*39
b) 37-x/3=x-13/7
37+13/7=x+x/3
272/7=4x/3
x=272/7:4/3
x=204/7
Bài 5:
a)x+37=50
⇔x=13
b)2x-3=11
⇔2x=14
⇔x=7
c)(2+x):5=6
⇔2+x=30
⇔x=28
d)2+x:5=6
⇔x:5=4
⇔x=20
a)x+37=50
x =50-37
x =13
b)2.x-3=11
2.x =11+3
2.x =14
x =14:2
x =7
c)(2+x):5=6
2+x =6.5
2+x =30
x=30-2
x=28
d)2+x:5=6
x:5=6-2
x:5=4
x=4.5
x=20
Câu trả lời nhớ ghi đầy đủ như này nha bạn
\(\dfrac{37\cdot5^4}{25^2}=\dfrac{37\cdot5^4}{5^4}=37\\ \dfrac{2^4\cdot2^6\cdot3^8\cdot9^2}{4^4\cdot3^{11}}=\dfrac{2^{10}\cdot3^8\cdot3^4}{2^8\cdot3^{11}}=2^2\cdot3=12\\ \dfrac{3\cdot9^4\cdot9^3}{3^2\cdot9}=\dfrac{3\cdot3^8\cdot3^6}{3^2\cdot3^2}=3^{11}\\ \dfrac{125\cdot5\cdot64-25^3\cdot10\cdot4}{5^7\cdot8}=\dfrac{5^3\cdot5\cdot2^6-5^6\cdot2\cdot5\cdot2^2}{5^7\cdot2^3}=\dfrac{5^4\cdot2^3\left(2^3-5^3\right)}{5^7\cdot2^3}=\dfrac{8-125}{5^3}=\dfrac{-117}{125}\)
\(5\left(3+x\right)+3\left(2+x\right)=37\)
\(\Leftrightarrow15+5x+6+3x=37\Leftrightarrow8x+21=37\)
\(\Leftrightarrow8x=16\Leftrightarrow x=2\)
5. (3+x ) + 3.(2+x) = 37
5.3 + 5.x + 3.2+3.x=37
15+5.x + 6+3.x= 37
5.x+3.x+15+6=37
5.x+3.x= 37 - 15-6
5.x+3.x= 16
x.(3+5)= 16
x.8=16
x= 16:8
x= 2